Pengaruh Kompetensi Profesional Guru terhadap Minat Belajar Pendidikan Agama Kristen Siswa - Mikha Agus Widiyanto; Andreas Fernando (Sekola Tinggi Teologi Sangkakala Jakarta, 2020)
Teacher plays an important role in improving student’s interest in learning. Teacher's competence is the key to his success in moving students towards increasing their interest in learning. Thorough the professional competencies possessed, teacher can deliver subject matter in the way that is easily understood by student and the ability to present interesting material through the use of instructional media can arouse students' interest in learning Christian Religious Education. The purpose of this study was to examine the effect of teacher professional competence on students' interest in learning Christian Religious Education. The quantitative research approach with the correlational method, with a total sample of 100 students. The results of the analysis indicate that the teacher's professional competence significantly influences students' interest in learning Christian Religious Education. Increasing interest in learning Christian Religious Education can be done by increasing the professional competence of teacher. Professional Christian Religious Education teacher has a set of competencies that support the realization of effective learning. Teacher’s professional competence contributes in realizing Christian Religious Education learning that can arouse student’s interest in learning.